Carbon nanotubes introduced in different phases of C/PyC/SiC composites: Effect on microstructure and properties of the materials. (12th August 2015) - Mei, Hui; Wang, Huwei; Zhang, Nan; Ding, Hui; Wang, Yuetang; Bai, Qianglai
Abstract: The present paper reports on the effects of carbon nanotubes (CNTs), introduced in different phases of carbon fiber-reinforced silicon carbide (C/SiC) composites, on the microstructure and properties of the material. In composites with CNTs deposited on C fibers (C/CNTs/PyC/SiC), a double-scale pull-out phenomenon, at the fiber and CNT level, was considerably more prominent than in their CNT-free counterparts; the effect was attributed to the weak CNT–PyC interface. The tensile strength and work of fracture of C/CNTs/PyC/SiC composites were found to increase by 67.3% and 107.2%, respectively, from the CNT-free case. The introduction of CNTs into the SiC matrix did not offer significant enhancement in the mechanical properties of the C/PyC/CNTs/SiC composites which exhibited brittle failure.